Mahatma Gandhi : the essential writings - Brown, Judith M. (Oxford, UK : Oxford University Press, 2008)
Drawn from the full range of Gandhi's published work--books, articles, broadcasts, interviews, letters--this superb selection illuminates his thinking on religion and spirituality, on society and its problems, on politics and British rule, and on non-violence and civil disobedience
Includes bibliographical references and index.
Keywords: Gandhi, -- Mahatma -- 1869-1948 -- Political and social views